“City Ordinances of the City of Needles.” The Needles Eye, November 29, 1913, p. 3. Chapter 4, Article 4—Concealed Weapons, §§ 60-61. Approved November 28, 1913. Volume 25, Number 48. (Needles, California) - (:unkn) unknown (General Publisher, 1913)
Prohibited concealed carry of pistol, revolver, dirk, derringer, dagger, Bowie-knife, razor, brass knuckles, slung-shot, sand-bag, or other dangerous or deadly weapon.
--
Keywords: CARRY - CONCEALED